1999
DOI: 10.1136/gut.44.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Rectal biopsy for diagnosis of intestinal neuronal dysplasia in children: a prospective multicentre study on interobserver variation and clinical outcome

Abstract: Background-Intestinal neuronal dysplasia (IND) of the colonic submucous plexus is considered to be a congenital malformation of the enteric nervous system causing symptoms resembling those of Hirschsprung's disease. In contrast with the established diagnosis of aganglionosis using enzyme histochemistry, controversy exists over the diagnostic criteria of IND on rectal biopsies previously defined by a consensus report and the causal relation between morphological findings and clinical symptoms. Aims-The interobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 39 publications
2
59
0
Order By: Relevance
“…The easiest means of obtaining adequate diagnostic tissue in rectal biopsies in infants is by rectal suction biopsy (RSB) (18). These provide larger and deeper biopsies than standard endoscopic forceps biopsies, which are usually inadequate to obtain sufficient submucosa and therefore are not recommended (19,72) (Fig. 2).…”
Section: Investigations Histopathologymentioning
confidence: 99%
“…The easiest means of obtaining adequate diagnostic tissue in rectal biopsies in infants is by rectal suction biopsy (RSB) (18). These provide larger and deeper biopsies than standard endoscopic forceps biopsies, which are usually inadequate to obtain sufficient submucosa and therefore are not recommended (19,72) (Fig. 2).…”
Section: Investigations Histopathologymentioning
confidence: 99%
“…The study of the ressected specimen of the intestine demonstrated alterations that were suggestive of the diagnosis of neuronal intestinal dysplasia. Although the existence of this nosocomial entity had been suggested at the fourth international symposium on Hirschsprung disease and related neurocristopathies, it is not clear if it is a separate primary entity or some sort of acquired condition [11,19]. Our cases were pre-school aged children with severe constipation and huge colonic dilatations with or without significant dilatation of the small bowel and duodenum.…”
Section: Discussionmentioning
confidence: 75%
“…Other morphological features, such as the presence of ectopic ganglion cells, increased acetylcholinesterase activity, ganglion cells with a "button" appearance and hypertrophy of the nerve trunks, are considered diagnostic criteria in some studies [9,10,16,68,79,91] . The criteria described by MeierRuge et al [22] (2004) and slightly altered by MeierRouge et al [5] [5,77,92] .…”
Section: Diagnosismentioning
confidence: 99%